The Effect Of Price, And Product Quality On Purchasing Decisions For Promag Drugs In Surabaya (Case Study on S1 Management Students at Sunan Giri University Surabaya) - Firdausiyah, Riski Arifah; Adawiyah, Robiatun; Munir, Misbachul (Peneliti.net, 2024)
The purpose of this study was to determine and analyze the effect of price and product quality on Promag purchasing decisions in Surabaya, where the intended object was S1 Management students at Sunan Giri University Surabaya. The research method used is quantitative method. The sample determined was 50 people, the data collection technique used a questionnaire and the analysis technique used was multiple linear regression analysis techniques. The results showed that price did not have a significant positive effect on Promag purchasing decisions in Surabaya. This shows that the price factor has not been able to play an important role in influencing consumer decisions to buy the promag. This means that price is no longer part of consumer priorities in buying promag drugs, because of course for healing all kinds of drugs will be purchased, as well as promag drugs. In contrast to product quality which has a positive influence on Promag purchasing decisions in Surabaya. This shows that consumer perceptions of the quality of Promag products have a significant impact on their decision to buy the ulcer drug.